PWE-069 Management of pancreatic fluid collections by LAMS: large series from a tertiary referral HPB centre. (June 2019) - (Geri) Keane, Margaret; El-Sherif, Yasser; Warner, Ben; Reffitt, David; Harrison, Phillip; Joshi, Deepak; Devlin, John
Abstract : Background: Endoscopic transmural drainage is increasingly accepted as the first-line treatment for patients with symptomatic pancreatic fluid collections (PFC). International data has shown that in comparison to double pigtail stents Lumen Apposing Metal Stents (LAMS) are associated with higher rates of clinical success (especially in cysts with necrosis), shorter procedure times and potentially fewer adverse events. To date there has been limited data from the UK on the utility of these stents. Methods: Between January 2016 - December 2018 all patients who required endoscopic drainage of a pancreatic fluid collection via EUS-guided LAMS (Hot AXIOS™ system, Boston Scientific) were included. Treatment success, length of hospital stay, adverse events, reinterventions and length of follow-up were recorded in each case. Results: During the 3 year study period, 84 EUS-guided LAMS were placed on 80 patients. Median age was 52 years (Range 7–79 years). 52% (44/84) were female. Necrotic material was present in 44% (37/84) and significant portal hypertension visible on EUS in 8% (7/84). In four patients a 8 mm stent was placed, 10 mm stents were placed in thirty-five patients, a 15 mm stent in twenty-five patients and a 20 mm stent in eleven patients (in nine patients the stent size was unknown). Adverse events occurred in 11% (9/84) of cases (6 cases of failed stent deployment, 2 buried stents and one recurrent pancreatic fluid collection following stent removal) Conclusion: Use of LAMSs in the management of pancreatic fluid collections was safe and effective and associated with low rates of cyst recurrence.